Comparison of quantitative determination for SBS content in SBS modified asphalt. (3rd May 2021) - Xu, Song; Fan, Yong; Feng, Zhengang; Ke, Yunbin; Zhang, Canlin; Huang, Heyao
Highlights: Three calibration curves for detecting SBS content were established. The priority for SBS content detection is FTIR, rheological, and physical tests. FTIR exhibits the most promising approach in quantitative determination of SBS content. Abstract: It is vital for the quality assurance of SBS modified asphalt to determine the SBS content accurately in modified asphalt. In the present work, radial and linear SBS were used to modify asphalt with different addition amount, then three calibration curves for detecting SBS content were established by linear regression based on the relationship between SBS content and physical, rheological and FTIR indexes of modified asphalts, respectively. The three methods were compared by focusing on the accuracy, feasibility and efficiency. Experimental results indicate that the physical, rheological and FTIR indexes all have strong correlation with SBS content, and linear regressions could be performed with the correlation coefficients from high to low: FTIR method, rheological property method and physical property method. The rheological and physical property methods are indirectly performance-based detection, so their accuracy of quantitative determination largely depends on the reliability of tests, and could be misled by substitute or additive. While the FTIR approach is established based on the FTIR peaks at 966 cm −1 and 699 cm −1, two characteristic functional groups of SBS molecule, which can directly reflect the amount of SBS modifier. In comparison with rheological and physical property methods, the FTIR method has many obvious advantages, such as less reagent and asphalt consumption, simpler sample pretreatment, rapider spectrum acquisition, more reliable result output, more accurate determination and so on. FTIR method exhibits the most promising approach in quantitative determination of SBS content in its modified asphalt.